Environmental DNA reveals tropical shark diversity in contrasting levels of anthropogenic impact - Bakker, Judith; Wangensteen, Owen S.; Chapman, Demian D.; Boussarie, Germain; Buddo, Dayne; Guttridge, Tristan L.; Hertler, Heidi; Mouillot, David; Vigliola, Laurent; Mariani, Stefano (Scientific reports, 2017)
Sharks are charismatic predators that play a key role in most marine food webs. Their demonstrated vulnerability to exploitation has recently turned them into flagship species in ocean conservation. Yet, the assessment and monitoring of the distribution and abundance of such mobile species in marine environments remain challenging, often invasive and resource-intensive. Here we pilot a novel, rapid and non-invasive environmental DNA (eDNA) metabarcoding approach specifically targeted to infer shark presence, diversity and eDNA read abundance in tropical habitats. We identified at least 21 shark species, from both Caribbean and Pacific Coral Sea water samples, whose geographical patterns of diversity and read abundance coincide with geographical differences in levels of anthropogenic pressure and conservation effort. We demonstrate that eDNA metabarcoding can be effectively employed to study shark diversity. Further developments in this field have the potential to drastically enhance our ability to assess and monitor elusive oceanic predators, and lead to improved conservation strategies.